2013
DOI: 10.1111/jpm.12042
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the quality of life of vulnerable young males with severe emotional and behaviour difficulties in a residential setting and young males in mainstream schooling

Abstract: One hundred and seventy-four males completed a quality of life (QoL) assessment utilizing, a generic paediatric quality of life inventory (PedsQL) and the short form (36) health survey (SF36). The adolescents aged 13-16 years were in a Scottish Centre for young males with social, emotional, behavioural and educational problems. To identify similarities and differences, a comparison group (n = 110) of males in the third and fourth year in a mainstream secondary school were also administered the PedsQL and the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In a study of 400 Norwegian youth in residential care, using the KNDL‐R instrument (Jozefiak & Kayed, ; Jozefiak et al, ), the authors reported that youth in residential care had poorer quality of life with regard to physical and emotional wellbeing, self‐esteem and peer relations, in comparison with patients in child and adolescent psychiatry and the general population. Damnjanovic et al () found a similar pattern in a study of 216 youths, 8‐ to 18‐year‐olds, who were in residential care in Serbia, using the Pediatric Quality of Life inventory, while Carroll, Duffy, and Martin (), in a study of 13‐ to 16‐year‐old young males in residential care in Scotland, found quite a similar quality of life among these young males in residential care as in the general population.…”
mentioning
confidence: 68%
“…In a study of 400 Norwegian youth in residential care, using the KNDL‐R instrument (Jozefiak & Kayed, ; Jozefiak et al, ), the authors reported that youth in residential care had poorer quality of life with regard to physical and emotional wellbeing, self‐esteem and peer relations, in comparison with patients in child and adolescent psychiatry and the general population. Damnjanovic et al () found a similar pattern in a study of 216 youths, 8‐ to 18‐year‐olds, who were in residential care in Serbia, using the Pediatric Quality of Life inventory, while Carroll, Duffy, and Martin (), in a study of 13‐ to 16‐year‐old young males in residential care in Scotland, found quite a similar quality of life among these young males in residential care as in the general population.…”
mentioning
confidence: 68%
“…The subjective component to an individual’s well-being [ 13 , 14 ] has not received the same attention as mental health and psychosocial problems [ 15 , 16 ]. We have only found seven publications addressing QoL among adolescents in child welfare [ 17 23 ], but two publications [ 21 , 22 ] were based on the same QoL data. Two studies [ 17 , 19 ] had a small sample size, limiting the generalizability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear, whether the Polish version of the KINDL was reliable. Only three studies included QoL reports from youths living in RYC [ 17 , 21 , 23 ]. Of these, only two were representative, allowing for comparisons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some findings are counterintuitive. Carroll, Duffy, and Martin (2014) found that quality of life in certain groups in residential care was higher than in adolescents from mainstream schools. The highest scores were reported among children in a day-group setting, followed by children in secure placements, while children from mainstream schools came third (comparison group), and the worst results were found among the young people in the residential group.…”
mentioning
confidence: 99%